2012
DOI: 10.1111/j.1365-3040.2012.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive strategies of Parietaria diffusa (M.&K.) to calcareous habitat with limited iron availability*

Abstract: The study of native plants growing in hostile environments is useful to understand how these species respond to stress conditions. Parietaria diffusa (M.&K.) is able to survive in highly calcareous soils and extreme environments, such as house walls, without displaying any chlorotic symptoms. Here, we have investigated the existence of Strategy I complementary/alternative mechanism(s) involved in Fe solubilization and uptake and responsible for Parietaria's extraordinary efficiency. After assessing the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 76 publications
(121 reference statements)
1
22
1
Order By: Relevance
“…It is crucial under alkaline conditions, which represent a major limiting factor for agricultural productivity worldwide. Furthermore, it is interesting to note that the specific adaptations of calcicole plants to calcareous substrates have been hypothesized to be at least in part dependent on a pronounced shift from classic strategy I responses towards phenolics secretion specifically under alkaline conditions [61]. This was observed for Parietaria diffusa , an Fe-efficient plant that can be found on walls and similar substrates in the Mediterranean, when effects elicited by Fe-free medium were compared to those of an alkaline carbonate medium.…”
Section: Discussionmentioning
confidence: 98%
“…It is crucial under alkaline conditions, which represent a major limiting factor for agricultural productivity worldwide. Furthermore, it is interesting to note that the specific adaptations of calcicole plants to calcareous substrates have been hypothesized to be at least in part dependent on a pronounced shift from classic strategy I responses towards phenolics secretion specifically under alkaline conditions [61]. This was observed for Parietaria diffusa , an Fe-efficient plant that can be found on walls and similar substrates in the Mediterranean, when effects elicited by Fe-free medium were compared to those of an alkaline carbonate medium.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, mixtures of NaCl and Na 2 CO 3 were added into the nutrient solution to mimic the concentrations that occur in saline-alkaline soil with a high Na + concentration and high soil pH. It has been reported that buffering pH to 8.3 leads to substantial precipitation of Fe along with other nutrients in a mural habitat (Donnini et al , 2012). In the current study, we also observed Fe precipitation from the saline-alkaline solution, resulting in a lower available Fe concentration (See Supplementary Table S1 at JXB online).…”
Section: Discussionmentioning
confidence: 99%
“…Two genes encoding Fe 2+ transporters, IRT1 (Bughio et al , 2002) and IRT2 (Ishimaru et al , 2006), have been isolated in rice plants. The addition of bicarbonate to growth medium has been demonstrated to cause foliar chlorosis in Parietaria diffusa , a Strategy I plant, due to reduction in Fe acquisition (Donnini et al , 2012). Lucena et al (2007) reported that bicarbonate induced foliar chlorosis and inhibited the expression of genes encoding FER-like transcription factors, thus inhibiting the expression of ferric reductase, iron transporter, and H + -ATPase genes in a number of Strategy I plants.…”
Section: Introductionmentioning
confidence: 99%
“…Plants were left into a half-nutritive solution for 10 days, in order to allow them to adapt to the growth conditions. Subsequently, stress treatments were imposed according to Donnini et al (2012). Acclimated plants were transferred into containers containing a modified nutritive standard solution according to the different conditions applied: (i) control (+Fe): 100 μM Fe-EDTA (pH 6 ~ 6.2); (ii) absence of iron (−Fe): 0 μM Fe-EDTA (pH 6 ~ 6.2); (iii) presence of Bicarbonate (FeBic): 100 μM Fe-EDTA, 10 mM NaHCO 3 , and 0.5 g/L CaCO 3 (pH 8.2 ~ 8.3).…”
Section: Methodsmentioning
confidence: 99%